Effect of Interval and Continuous Training on the Athlete’s Aerobic Fitness level - Getnet Tasew, Daniel (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2021)
The purpose of this study was to compare the effect of continuous and interval training on athlete’s aerobic fitness level. To meet this objective experimental research design was used. For this study 30 middle and long distance athletes were selected as a subject. All these athletes were divided into two different groups (continuous group (CG) and interval group (EG)) based on their pretest results. To see the effect of these training methods and to analyze whether there is a significant different between athlete’s aerobic fitness level after 12 weeks intervention, paired and independent sample t- test with an alpha value of .05 was employed. Furthermore, to examine the magnitude of observed differences between groups, effect sizes (Cohen’s d) were calculated. Finally, Results in this study showed that interval training group showed significant improvements in aerobic fitness level better than continuous training group. I.e. , in Astrand treadmill test the mean VO2max score of interval group was 76.81 ± 1.87 and 68.44 ± 3.14 for continuous group with P = .032 ; in 2.4 Km run test the mean time for interval group was 0:07:21 ± 0:00:27 and 0:08:05 ± 0:01:00 for continuous group with P = .017 ; in 20m beep incremental test the mean result for interval group was 17.74 ± .38 and 15.93 ± 2.93 for continuous group , P= .045. Then, it was concluded that interval training method was beneficial in improving athlete’s aerobic fitness level than continuous training method